2012
DOI: 10.1186/1748-717x-7-164
|View full text |Cite
|
Sign up to set email alerts
|

A single-institution study of stereotactic body radiotherapy for patients with unresectable visceral pulmonary or hepatic oligometastases

Abstract: PurposeThe purpose of this study is to evaluate the feasibility, efficacy and toxicity of SBRT for treatment of unresectable hepatic or lung metastases regardless of their primary tumor site for patients who received prior systemic chemotherapy.Methods and materialsBetween July 2007 and June 2010, 90 patients were treated with the CyberKnife® SBRT system for hepatic or pulmonary metastatic lesions. Medical records were retrospectively reviewed. The endpoints of this study were local control, overall survival (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
28
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(29 citation statements)
references
References 18 publications
1
28
0
Order By: Relevance
“…At our institution, a similar dosing schedule is used for patients who present with oligometastatic lung and liver metastases. Various fractionation schedules have been reported for patients treated for lung [2325] and liver metastases [13,26,27]. Dose escalation was reported to improve local control rates in a phase I dose-escalation trial of hepatic metastases from Rule et al The study randomized 27 patients to 30 Gy in 3 fractions, 50 Gy in 5 fractions, and 60 Gy in 5 fractions [12].…”
Section: Discussionmentioning
confidence: 99%
“…At our institution, a similar dosing schedule is used for patients who present with oligometastatic lung and liver metastases. Various fractionation schedules have been reported for patients treated for lung [2325] and liver metastases [13,26,27]. Dose escalation was reported to improve local control rates in a phase I dose-escalation trial of hepatic metastases from Rule et al The study randomized 27 patients to 30 Gy in 3 fractions, 50 Gy in 5 fractions, and 60 Gy in 5 fractions [12].…”
Section: Discussionmentioning
confidence: 99%
“…At our institution, a similar dosing schedule is used for patients who present with oligometastatic lung and liver metastases. Various fractionation schedules have been reported for patients treated for lung [23][24][25] and liver metastases [13,26,27]. Dose escalation was reported to improve local control rates in a phase I dose-escalation trial of hepatic metastases from Rule et al The study randomized 27 patients to 30 Gy in 3 fractions, 50 Gy in 5 fractions, and 60 Gy in 5 fractions [12].…”
Section: Discussionmentioning
confidence: 99%
“…However, unlike our analysis the study was not restricted to lesions of colon primary. Fumagalli et al suggested a difference in outcome based on anatomical location [26]. The study assessed outcomes in hepatic or pulmonary oligometastases of which 70% were of digestive primary.…”
Section: Discussionmentioning
confidence: 99%
“…In general, patients with up to four metastases, and with the maximum diameter of the largest metastasis of no more than 40 mm, are selected for the SBRT treatment. 28 However, some authors describe treatment procedures performed for 110-mm hepatic metastasis 3,15 that are also applicable to patients with metastases in two organs. The SBRT requires a highly precise dose planning and delivery.…”
Section: Discussionmentioning
confidence: 99%